Supine Percutaneous Nephrolithotomy: PRO - Falahatkar, Siavash; Allahkhah, Aliakbar; Soltanipour, Soheil (Urology Journal, 2011)
Purpose: To share the experience of the authors with the urological family in the world by the review of literature on supine percutaneous nephrolithotomy (PCNL). Materials and Methods: We have searched all the available databases, including PubMed or MEDLINE and Embase Biomedical Database to find any English articles related to supine PCNL from 1998 to 2010. Of 17 studies, 11 were case series and 6 were comparative. Results: A total of 1914 patients were studied. Only the results of mean operation time were significant. Supine PCNL offers several advantages, including less operation time, less patient handling, needing only one drape, easier access to the urethra and upper calyces, facilitation of drainage of stone fragment with the Amplatz sheath, less anterior kidney displacement due to lying the kidney in its normal anatomical position, less risk of the colon injury, more tolerable for the patients with pulmonary or cardiovascular disease, and better for morbid obese patients. The overlap density of the vertebrae in the semi-supine position can be avoided. Furthermore, the fluoroscopy tube is far from the puncture site; thus, the space is open for the surgeon to work and the surgeon can perform the procedure in a more comfortable seated position. Conclusion: The study showed that PCNL in the supine position is feasible. Although supine PCNL has numerous advantages, it is not routine in many surgical centers throughout the world. The practice of supine PCNL will be popular when the academic centers be encouraged to start it.